2020
DOI: 10.1039/d0bm00896f
|View full text |Cite
|
Sign up to set email alerts
|

3D printing of high-strength chitosan hydrogel scaffolds without any organic solvents

Abstract: 3D printing of chitosan hydrogel has attracted wide interests because of its excellent biocompatibility, antibacterial activities, biodegradability, none-toxicity and low cost. However, chitosan inks are often involved in toxic and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(49 citation statements)
references
References 43 publications
1
43
0
Order By: Relevance
“…[ 9 ] Thus it is very important to optimize the formula and discuss the performances of the precursor hydrogel inks. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 9 ] Thus it is very important to optimize the formula and discuss the performances of the precursor hydrogel inks. [ 10 ]…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the inflammatory factors (e.g. tumor necrosis factor-α (TNF-α), interleukins 1β and 6 (IL-1β and IL-6)) after implanting vascular scaffolds can be measured by ELISA [ 174 ]. And the degradability is verified by the weight reduction of scaffolds after placed in culture mediums after some days.…”
Section: Transformation Of Vascular Scaffolds To Clinical Productivitmentioning
confidence: 99%
“…16 Zhou et al printed chitosan presolution (alkali solution) using a high-temperature method. 17 However, the long fabrication time and the use of acidic or alkaline media to dissolve the chitosan pre-gel solution in these methods render it unsuitable for direct cell encapsulation and biomedical application. Alternatively, Liu et al reported a 3D printed chitosan-based hydrogel using photocrosslinking of phenol functionalized chitosan and dibenzaldehyde-terminated telechelic poly(ethylene glycol) (DF-PEG) pre-gel crosslinked by dynamic imine bonds.…”
Section: Introductionmentioning
confidence: 99%